The open mobile alliance : - Brenner, Michael (John Wiley, 2008)
The Open Mobile Alliance (OMA) is an industry forum, which develops open specifications to help in the creation of applications and services to be deployed over converged networks. The alliance is the leading industry forum for generating market-driven specifications for interoperable mobile service enablers that facilitate global user adoptions of mobile multimedia services. Members include traditional wireless industry segments, such as mobile operators mobile operators (e.g. AT&T, China Mobile, Orange, Sprint Nextel, T-Mobile, Telefonica, Vodafone), equipment and mobile systems manufacturers (e.g. Alcatel-Lucent, Ericsson, Motorola, Nokia, Philips, Samsung, Siemens, Sony-Ericsson), and Information Technology vendors (e.g. BEA Systems, IBM, Microsoft, Oracle Corporation, Sun Microsystems and NEC). Since its formation in 2002, the OMA has made significant progress in areas such as push-to-talk over cellular, device management, presence and group management, and messaging.